THE HOUSEHOLD FINANCIAL CONDUCT AND ITS IMPACT ON STABILITY FINANCIAL SYSTEM - Selamat Zebua; Sugina Sugina; Nitema Gulo (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The importance of maintaining Financial System Stability is the basis for economic sustainability. One of the pillars of national economic resilience is the role of the household sector as a fundamental object so that supply and demand reach an equilibrium point. Household financial behavior is closely related to income levels and household credit behavior towards Financial System Stability. Therefore, the aim of this study is to determine whether there is an effect of financial behavior in the household sector on financial system stability. Data collection using purposive sampling method was carried out using a questionnaire through the help of GoogleForms application to 400 households in the Tangerang area. The analytical tool used is Structural Equation Modeling (SEM) with SmartPLS 3. 0 to explain the correlation between endogenous and exogenous variables. The loading factor results indicate that the value of financial behavior is 0.285, household income is 0.232 and household credit behavior is 0.229 has a significant effect on the financial stability system. Meanwhile, the value of financial behavior is 0.599 on household income and the value of financial behavior is 0.588 on household credit behavior which has a direct effect.